2022
DOI: 10.1002/pat.5918
|View full text |Cite
|
Sign up to set email alerts
|

Modeling heat transfer and transcrystallization kinetics during processing of polymer‐based composites materials

Abstract: Transcrystallization phenomena is a key issue to master for better understanding the role on the fiber‐matrix interface in composites materials behavior during and after processing. In this paper, a non‐isothermal kinetics model is presented to consider crystallization in fiber‐based composite with thermoplastic matrix. The model extends Schneider's formulation to describe the development of transcrystalline layers around fibers. It also mentions the possibility to easily account for shear and flow conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The past decades have seen expansion of the application of composite materials in industrial components and structures due to their lightweight and high specific mechanical performance 1,2 . However, traditional fabrication technologies limited the manufacturing of complex structures 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The past decades have seen expansion of the application of composite materials in industrial components and structures due to their lightweight and high specific mechanical performance 1,2 . However, traditional fabrication technologies limited the manufacturing of complex structures 3 .…”
Section: Introductionmentioning
confidence: 99%
“…4,6−10 For example, Wang et al 7 found that the crystal texture and interfacial structure of poly(ether−ether−ketone)-carbon fiber composite are sensitive to crystallization conditions and processes. Bigot et al 8 presented a nonisothermal kinetics model to describe the crystallization in fiber-based composite. Ning et al 4 summarized the research about the interfacial crystallization to enhance semicrystalline polymer/filler interfacial interaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fiber-induced crystallization has been extensively reported in the literature for a long time, in the fields of crystallization behavior, material properties, kinetic models, etc. , For example, Wang et al found that the crystal texture and interfacial structure of poly­(ether–ether–ketone)-carbon fiber composite are sensitive to crystallization conditions and processes. Bigot et al presented a nonisothermal kinetics model to describe the crystallization in fiber-based composite. Ning et al summarized the research about the interfacial crystallization to enhance semicrystalline polymer/filler interfacial interaction.…”
Section: Introductionmentioning
confidence: 99%